PsycEXTRA Dataset
DOI: 10.1037/e504682010-001
|View full text |Cite
|
Sign up to set email alerts
|

Plateau in Muscle Blood Flow During Prolonged Exercise in Miniature Swine

Abstract: SUMMARTMuscle blood flov remained unchanged during pro'longed exercise when pigs were cooled by skin wetting and a fan. This muscle blood flov response was comparable to that of humans exercising under similar conditions. The effect of temperature on this response i's uncertain-since both increases and decreases in muscle blood flow have been reported during thermal stress.Svine were similar to humans in regulatinj blood flow distribution during prolonged exercise.Cardiovascular drift in swine differs from tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…However, muscle blood flow measured by Armstrong et al was actually quite constant in most muscles until 30·min of exercise, which was close to the time the animals fatigued (Armstrong et al, 1987b). A subsequent study with this same species showed that muscle blood flow remains constant as long as body temperature is maintained (McKirnan et al, 1989). In humans under certain exercise conditions, blood flow increases with exercise duration, but this increased flow correlates well with an increase in muscle V O 2 (González-Alonso, 1998; Ferguson et al, 2001).…”
Section: Variation In Blood Flow With Exercise Durationmentioning
confidence: 95%
“…However, muscle blood flow measured by Armstrong et al was actually quite constant in most muscles until 30·min of exercise, which was close to the time the animals fatigued (Armstrong et al, 1987b). A subsequent study with this same species showed that muscle blood flow remains constant as long as body temperature is maintained (McKirnan et al, 1989). In humans under certain exercise conditions, blood flow increases with exercise duration, but this increased flow correlates well with an increase in muscle V O 2 (González-Alonso, 1998; Ferguson et al, 2001).…”
Section: Variation In Blood Flow With Exercise Durationmentioning
confidence: 95%
“…This is the first study to demonstrate significant reductions in blood flow to exercising skeletal muscle during prolonged exercise in humans. Previous studies in humans (Kirwan et al 1987;Nielsen et al 1990Nielsen et al , 1993Nielsen et al , 1997, rats (Laughlin & Armstrong, 1983) and miniature swine (Armstrong et al 1987;McKirnan et al 1989) have shown that blood flow to active muscles is either maintained or increased when heat stress is superimposed during exercise. This is in contrast to the significant reductions in blood flow to some exercising muscles found in sheep with heat stress (Bell et al 1983).…”
Section: Discussionmentioning
confidence: 99%